2023
DOI: 10.1021/acs.energyfuels.3c00410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Engineered Biochar-Based Catalysts for Syngas Production in a Biomass Pyrolysis and Catalytic Reforming Process

Abstract: Biochar, originating from biomass pyrolysis, has been proven a promising catalyst for tar cracking/reforming with great coke resistance. This work aims to evaluate various engineered biochar-based catalysts on syngas production in a biomass pyrolysis and catalytic reforming process without feeding extra steam. The tested engineered biochar catalysts include physical-and chemical-activated, nitrogen-doped, and nickel-doped biochars. The results illustrated that the syngas yields were comparable when using bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The first phase of the process is to expel moisture and volatile substances from the biomass structure; hence, more moisture is expelled from the DBC feedstock when the temperature rises (Table 2). Initially, the VM content and tarry vapors (such as CO, CO2, CxHy, CxHyOz, H2O, HCN, and NH3), which are associated with cellulose and hemicellulose contents [15,60,83], were excreted from feedstocks [23], which resulted in the majority of mass loss [45,88], inducing bond rupture and the generation of hydroperoxide, -COOH and -CO groups [13,35,40]. The results showed that increasing the pyrolysis for 20 min of holding time from 400 °C to 500 °C significantly decreased the MC and VM contents of DBC biochar from 2.18% to 1.66% and 28.72% to 19.23%, respectively.…”
Section: The Vm MC Ash Fc and Ph Of Dbc Biochar Obtained From Various...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first phase of the process is to expel moisture and volatile substances from the biomass structure; hence, more moisture is expelled from the DBC feedstock when the temperature rises (Table 2). Initially, the VM content and tarry vapors (such as CO, CO2, CxHy, CxHyOz, H2O, HCN, and NH3), which are associated with cellulose and hemicellulose contents [15,60,83], were excreted from feedstocks [23], which resulted in the majority of mass loss [45,88], inducing bond rupture and the generation of hydroperoxide, -COOH and -CO groups [13,35,40]. The results showed that increasing the pyrolysis for 20 min of holding time from 400 °C to 500 °C significantly decreased the MC and VM contents of DBC biochar from 2.18% to 1.66% and 28.72% to 19.23%, respectively.…”
Section: The Vm MC Ash Fc and Ph Of Dbc Biochar Obtained From Various...mentioning
confidence: 99%
“…According to the meta-analysis literature, biochar is recognized as a potential material for achieving environmental sustainability due to its unique properties and diverse applications, which include agricultural applications that can reduce greenhouse gas emissions [6][7][8] and achieve carbon capture and storage [9,10], in addition to achieving increases in soil fertility and enhancing crop productivity [11,12]. Moreover, biochar has the potential to be applied as a catalyst [13], an adsorbent [14], and for energy storage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Biorefineries are also anticipated to decrease greenhouse gas emissions and ease the energy crisis, 5,6 while offering economic opportunities for agriculture and forestry industries, organic waste management, and production of liquid fuels, platform chemicals, and carbon-neutral energy. 7 Global annual production of LCB is estimated at 181.5 billion tons with potential supplies being provided by various sectors. 8,9 LCB is a heterogeneous organic matrix with a three-dimensional structure that is primarily composed of lignin, cellulose, and hemicellulose, as well as a few other minor components, such as minerals and extractives.…”
Section: Introductionmentioning
confidence: 99%
“…Biorefineries are also anticipated to decrease greenhouse gas emissions and ease the energy crisis, 5,6 while offering economic opportunities for agriculture and forestry industries, organic waste management, and production of liquid fuels, platform chemicals, and carbon-neutral energy. 7 Global annual production of LCB is estimated at 181.5 billion tons with potential supplies being provided by various sectors. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the Ni-based catalysts have attracted much more attention. Taking into account the endothermic nature of the steam reforming reaction, the catalysts usually exhibit excellent activity at high temperatures with tar completely converted and a high yield of syngas and H 2 produced. However, Ni-based catalysts are prone to rapid deactivation due to sintering of active components and carbon deposition . Currently, the research focus in this field has gradually shifted to the design of catalysts with high activity and high stability to achieve complete conversion of biomass tar at lower catalytic temperatures. , …”
Section: Introductionmentioning
confidence: 99%